Seed Source Variation in Bauhinia purpurea L. - Irengbam, Michelle; Thapliyal, Manisha (Indian Forester, 2016)
The variations among the seed sources have been studied in many plant species to determine the best source so as to use it for various breeding purposes. The present study pertains to the seed source variation in Bauhinia purpurea, an important fodder tree species with high nutritional value having medicinal properties such as antioxidant and antibacterial among others. Seeds from 10 different sources in Uttar Pradesh and Uttarakhand were collected and studied for variations in different seed parameters viz. purity, germination per cent and moisture content, and seedling parameters viz., seedling growth and vigour. The seeds from Muzzafarnagar and Mohkampur sources performed best among all the seed sources studied and are recommended for plantation and other purposes in the region.